Carbohydrate ingestion impacts on male trap shooting performance - Braakhuis, A.; Harden, D.; Nottle, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Researchers have demonstrated that consumption of a carbohydrate solution during prolonged exercise enhances performance, but the effect of these supplements on shooting sports is unclear. The aim of this study was to determine the effect of a carbohydrate solution on performance in the sport of Olympic Trap shooting. In a double-blind, balanced, crossover design, eight fasted Olympic Trap shooters (mean ± SD: age 33.0 ± 15.9, weight 91.9 ± 21.7 kg) were required to ingest a liquid form of glucose or similarly flavoured placebo throughout a simulated shooting performance, following an overnight fast. Glucose content was 7.6% in a total volume of 1300 millilitres, with 100 millilitres being consumed every 10 minutes. Blood glucose levels were tested every 15 minutes. Each shooter completed three rounds of 25 targets, 20 minutes apart in one testing session. Changes between conditions for the same time interval, and for performance and blood glucose levels across time intervals were analysed. No significant blood glucose changes (p>.05) were seen in the placebo group. Blood glucose results were elevated from fasting levels and were significant in the final round (p<.05). No significant changes in performance were seen between the two drink groups (glucose score (mean ± SD) 56 ± 5; placebo score 54 ± 7). Prior to commencing the study all shooters completed a baseline shooting score under non-fasted conditions. The performance scores for shooters whilst consuming both drinks were only ever reduced from baseline (baseline score 61 ± 7), hence average scores across the time intervals never exceeded their average baseline performance. Despite no statistical change in performance it is shown that limiting your glucose intake negatively affects scoring consistency represented by first barrel, second barrel and lost targets. Whether this is indicative of cognitive performance would require further research.